DEVELOPMENT OF PROBLEM CHILDREN THROUGH THE GAPURA PANCA WALUYA PROGRAM FROM THE PERSPECTIVE OF CHILDREN'S RIGHTS PROTECTION - Rizqie Achmad Alfarezi (RADJA PUBLIKA, 2026)
The Gapura Panca Waluya program, initiated by the Governor of West Java through Circular Letter Number 45/PK.03.03/KESRA, is a policy for fostering troubled children through a semi-military approach involving cooperation with the Indonesian Army. This policy has drawn serious attention considering that the categorization of